STRATEGI PEMBELAJARAN INQUIRY SOSIAL DAPAT MENINGKATKAN HASIL BELAJAR TENTANG PENINGGALAN SEJARAH HINDU DI INDONESIA PADA MATA PELAJARAN IPS SISWA KELAS V SDN 194 PATAMPANUA - HASNAH, HASNAH (Kuriositas: Media Komunikasi Sosial dan Keagamaan, 2015)
Inquiry social learning Strategy is a Method applied to improve student learning outcomes. For this strategy, researcher conducted 3 Cycle to review Seeing strategy development Success rate singer. Where in CYCLE I Researcher do planning, Implementation, observation and reflection. The results showed that knowledge students Still Really was low.its proved by results of data analysis and reflection that has carried on Implementation of the action on cycle 1 Not referring at set Indicators That More Than 75% or follow the whole of Students Learning activities. While the findings in the cycle II No one got 100 score, only 7 students got 75-90 score or 63.63% andonly 3 students got 60-70 score or 27.27%. On cycle III, improving student learning outcomes on the material of Historical Hindu in Indonesia are optimaluccess. Every Final Evaluation Study shows that theaverage score in cycle 1 reached an average of 5.45%,where in the CYCLE II reached an average of 7.27%. While Scores in cycle III reached an average of 9.27%.